The Incidence of Impacted Maxillary Canines in a Kosovar Population. (8th July 2014) - Gashi, Ali; Kamberi, Blerim; Ademi-Abdyli, Resmije; Perjuci, Ferijale; Sahatçiu-Gashi, Arjeta
Abstract : Aim . The purpose of this study was to investigate the incidence of impacted maxillary canines in a Kosovar population. Materials and Methods . The study consisted of a retrospective analysis of the records of 8101 patients treated in the University Dentistry Clinical Center of Kosovo between August 2001 and February 2004. The chi-squared test was used to examine potential differences in the distribution of impacted maxillary canines stratified by gender, age, location (left or right), and position. P < 0.05 was accepted as statistically significant. Results . It was found that the incidence of impacted maxillary canines was 1.62%. Of the 131 impacted maxillary canines, 101 were in female patients and 30 were in male patients, a statistically significant difference. Ages were in the range of 9 to >20 years, with a mean age of 24.38 ± 8.09  years. Of these subjects, 99 (75.57%) had unilaterally impacted maxillary canines, while 32 (24.43%) had bilateral impactions, a statistically significant difference (P < 0.00002 ). Impacted canines in 92 subjects (70.2%) were palatally placed, and 18 (13.7%) were labially placed. This difference was also statistically significant (P < 0.00001 ). Conclusion . The incidence of impacted maxillary canines in the sample Kosovar population was 1.62%, which is comparable to the findings from previous studies.